Response of bacterial communities in Barents Sea sediments in case of a potential CO2 leakage from carbon reservoirs. (September 2020) - Borrero-Santiago, A.R.; Ribicic, Deni; Bonnail, Estefania; Netzer, Roman; Koseto, Deni; Ardelan, M.V.
Abstract: Carbon capture and storage sites in Barents Sea shelf are currently in progress as part of climate change mitigation activities. However environmental impacts of a possible CO2 seepage on bacterial community are lacking knowledge. This work addressed potential consequences on bacterial communities from Snøvit region in Barents Sea sediments. Long-term experiment (92 days) was carried out mimicking realistic conditions of pressure (∼30 bars) using the unique hyperbaric chamber (Karl Erik TiTank). The experiment was divided in three stages: i) 21 days of no CO2, ii) 50 days of simulation of carbon dioxide leakage (depletion of pH to 7.0) and iii) 14 days emulating a leakage cessation. Results suggested that bacterial communities can adapt to a CO2 leakage in short term. However, bacteria showed negative effects in terms of activity, community structure, and number of cells after long term CO2 exposure. After CO2 leakage cessation, bacterial communities did not show a significant recovery. These findings highlighted that, even though marine bacteria showed adaptation to the new conditions (acidified environment), in case of a small but continuous CO2 leakage marine bacteria might not be recovered upon pre-exposure status. Highlights: Simulation of real conditions of a CCS site are essentials for environmental risk assessments. Marine bacteria may adapt to a new situation in case of acidification event for a short time. Marine bacteria community is altered in case of a CO2 leakage after 3 weeks in long-term simulation. Results did not show a potential recovery of marine bacteria when CO2 was stopped within the monitored period.